Perceived status towards COVID-19 mitigation measures among medical students in Malaysian Borneo - Marieanne Florence; Ateeqah Abdul Said; Chong, Wen Jing; Jaya Dhaarshini Sundara Rajan; Karrthigeyan Ramachandaran; Muhamad Luqman Hakim Mohd Yamin; Nur Syahierra Azmi; Yeap, Jia Han; Azman Atil @ Azmi; Awang Setia Musleh; Azizan Omar; Mohd Yusof Ibrahim (Penerbit UMS, 2021)
Introduction: Mitigation measures are important in curbing COVID-19 infection. However, people’s adherence to the control measures is depending upon their knowledge, attitudes and practices (KAP) towards the disease. This study aims to determine the KAP on COVID-19 and its associated factors among medical students in Malaysian Borneo during the period of the pandemic. Methods: A cross-sectional online survey of 248 medical students from University Malaysia Sabah was conducted from August to September 2020. The survey instrument was adapted from a previously validated questionnaire on COVID-19. Descriptive statistics and simple logistic regression were conducted. Results: The mean age of respondents was 22.0 (SD 1.4) years. Majority (65.7%, n= 163) were clinical students, female gender (70.6%, n= 175), and Bumiputera ethnic (46.8%, n= 116). 211 (85.1%), 191 (77.0%) and 163 (65.7%) of the respondents have good level of knowledge, positive attitude and good practice respectively. Conclusion: The medical students are updated with the current health issues especially on COVID-19. They are aware of the attributes of the disease and have concerns in taking good care of themselves. Further study needs to be implemented among the groups of non-medical student of the same institution to compare their KAP on COVID-19.